Deputation to the Minister of Health - National Anti-Vaccination League (Great Britain) (London : National Anti-Vaccination League)
1929 1920s 12 pages THE VACCINATION INQUIRER - (Supplement) August. i Deputation to the Minister of Health. On Tuesday, 16th July, at noon, Mr. Greenwood, Minister of Health, received a Deputation from the National Anti-Vaccination League, at the Ministry of Health offices in Whitehall. The following took part in the Deputation to the Minister: Mr. Charles Wicksteed, J.P., of Kettering; the Right Rev. R.J. Tilson ; Mr. H.G. Chancellor ; Lady Isabel Margesson ; Lady Heath ; Mrs. Hedley Thomson ; Mr. Oswald Earp, M.A. ; Miss R. Lowther Crofton ; Mr. H.E. Ponting ; Mr. George Newman, of Gloucester ; Mr. de Vere Summers ; Mrs. Robinson Guppy ; Mrs. Arthur Butcher and Miss Pamela Butcher ; Mrs. Dixon Davies ; Miss Frances Cobbe; Mr. J. Gilbertson ; Mr. J.A. Skelton ; Mr. G.A. Garreau, of Clare College, Cambridge ; Mrs. Garreau ; Dr. Walter Walsh, M.A. ; Mr. W.H. Webb, of Southport ; Mr. John Silver; Mr. T.H. Smith ; Mr. Alexander Brown ; Lieut.-Colonel Donegan ; Major Reginald Austin ; Captain E.T. MacMichael ; Dr. H.B. Knight Chorley ; Dr. T.A. Vawdrey ; Mr. A. Long Brown ; Mr. Jos. Harrison ; Mr. H. Cromwell Wall ; Mr. F.E. Potter ; Dr. H. Tudor Edmunds ; Mr. G.C. Graves ; Mr. M. Beddow Bayly ; Miss M. Bradish ; Mrs. W.R. Anderson ; Mr. Alex. Paul ; Mr. Holford Knight, M.P. ; Mr. Francis Broad, M.P. ; Mr. Tom Groves, M.P. ; Mr. Peter Freeman, M.P. ; Mr. Arnold Lupton ; the Duchess of Hamilton ; Miss Lind-af-Hageby ; and Miss Loat. Letters of regret at inability to accompany the deputation were received from a large number of Members of Parliament, and from Lady Maud Warrender, the Marchioness of Donegall, the Earl of Dysart, Lady Lees, Mrs. F. Cavendish Bentinck, Dr. H. Fergie Woods. Dr. Herbert Snow, Dr. Alice Ker, Dr. Stirling Saunder, Mr. Arthur Trobridge, Major Gundry, J.P., Mr. Jos. P. Swan, Mr. Scott Duckers, Mr. Robert Brown, Miss A. Leigh Browne, J.P., Mr. W. Ralph Hall Caine, Mr. J.C. Swinburne-Hanham, J.P., Mr. G.C. Cope, Mr. W. Stebbings, Mr. Charles Gane, J.P., Aladame Drakoules, and many others. Mr. E.T. Wise, M.P. for Leicester East, had promised to introduce the Deputation, but he was detained at an important meeting of his Party. Mr. Francis T. Broad. M.P., took his place, and informed the Minister that there would be three speakers, Mr. H.G. Chancellor, Dr. M. Beddow Bayly, and Mr. Arnold Lupton. He introduced them in turn. The following are the speeches as read to the Minister :— Mr. Chancellor :— This Deputation from the Council of the National Anti-Vaccination League represents the opinions of voters in all parts of Great Britain who oppose vaccination and protest against its infliction by law, and the use of their money by the State to subsidise a practice condemned alike by their judgment and conscience. They authorise me as their mouthpiece to give you some reasons for the immediate repeal of the Vaccination Acts and to ask you to take steps to that end at the earliest opportunity possible. The statistics of your own department prove that more than half the parents of the country are behind us, and we have reason to believe that more than 90 per cent. of the members of your Party in the House of Commons agree with those parents, including the Prime Minister himself and some members of his Cabinet. Whilst we raise no objection here to its practice by those who believe in vaccination, we do object most strongly to its State establishment, endowment and enforcement upon those who regard it as both useless and dangerous. If vaccination really protects against smallpox, those so protected need not fear contact with it. If, as we contend, it does not protect, but involves danger to health and life, any degree of compulsion violates the liberty of the subject to secure his own health and that of his children against the artificial introduction of diseased matter into their system, a right that is elementary in a country claiming to be free. So far as adults are concerned, the State tacitly admits this, for it has never dared to enforce re-vaccination upon them, though even pro-vaccinists admit that primary vaccination is almost a farce and its protection only temporary. Only helpless infants are compelled to undergo the danger and suffering. It is their right we defend, and we appeal hopefully to you as Minister of Health in a Labour Government to protect from an unjust law these voteless sufferers, most numerous amongst the working class, by repealing it. A great question not a small one. Among the many urgent questions before the Government this one may appear small. It is really great, and involves great principles affecting parental liberty, public health, the right of private judgment, and the use of public money to enforce upon all a medical superstition devoid of scientific proof, believed in by some and rejected by most. 36/H24/24